VD_FINDINFO Jug / 2016 / 50 vom 5. Oktober 2015 - VD Tribunal cantonal (2015)
LÉSION CORPORELLE GRAVE, DOMMAGES À LA PROPRIÉTÉDROIT PÉNAL, MENACEDROIT PÉNAL, CONSTATATION DES FAITS | 122 CP, 144 CP, 180 CP, 46 al. 2 CP